A Critical Discourse Analysis of Women Leadership within Feminism in the "Cruella" Movie - Agata Cintya Nirmala; Christina Maya Iriana Sari (Humaniora Scientia, 2025)
The research discusses women's leadership within feminism through the three-dimensional framework of Fairclough's Critical Discourse Analysis (CDA). This study uses a qualitative descriptive research method that analyzes utterances in dialogues or monologues, and movie scenes related to women leadership. From the analysis by using the textual practice, it is concluded that the two characters of female leaders, Cruella and Baroness both have leadership traits that are reflected in their dialogue. The dialogue is categorized into types of sentences, namely descriptive, interrogative, imperative, and exclamative sentences, along with the use of pronouns and modality. The discursive practice influences the production process so it affects the text production and characterization of the characters in their positions as leaders. In addition, sociocultural practice shows how women leadership in the movie is influenced by real social phenomena related to women in the work field at that time and shows how women take masculine behavior to suit the work environment, like confidence, ambition, and competitiveness. Furthermore, by highlighting the assertive leadership traits of these characters, this movie provides a nuance of opposing the patriarchal system, thus showing how women are able to become leaders and succeed in breaking down societal norms.